The voices [videorecording (DVD)] - Reynolds, Ryan; Arterton, Gemma; Kendrick, Anna ([Publisher not identified], 2015)
Jerry is that chipper guy clocking the nine-to-five at a bathtub factory, with the offbeat charm of anyone who could use a few friends. With the help of his court-appointed psychiatrist, he pursues his office crush. However, the relationship takes a sudden, murderous turn after she stands him up for a date. Guided by his evil talking cat and benevolent talking dog, Jerry must decide whether to keep striving for normalcy, or indulge in a much more sinister path.